DBD, Iklim, Suhu, Kelembaban, Cu Hubungan Iklim (Suhu, Kelembaban dan Curah Hujan) dengan Kejadian Demam Berdarah Dengue (DBD) di Kota Tangerang Selatan Tahun 2016 – 2020 - Trisnowati Putri, Vivinda (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Climate change is one of the hot issues discussed recently, given its serious impact on various aspects of life, especially health. Climate change can increase the risk of disease occurrence due to increases in air temperature, air humidity, and extreme rainfall incidence. Climate change is one of the factors contributing to the increase in dengue cases. The purpose of this study is to determine the relationship between climate and DHF in South Tangerang City in 2016-2020. This research is a descriptive research using time series analysis of ecological study design. This research is included in the observational study that uses secondary data by looking at climatic factors, such as air temperature, humidity, and rainfall as independent variables and the incidence of DHF as a dependent variable. revealed that there was no very weak significant relationship in a negative direction (p = 0.346 / r = -0.124) between temperature and the incidence of DHF, there was a moderate relationship in a positive direction (p = 0.0005 / r = 0.470) between humidity and the incidence of DHF, and there is a moderately significant relationship in a positive direction (p = 0.016 / r = 0.309) between rainfall and the incidence of DHF. Humidity and rainfall have a significant relationship with the incidence of DHF in South Tangerang City in 2016-2020.